Sistem Rekomendasi Pemilihan Keramik Berbasis Android Menggunakan Metode Fuzzy MCDM dan SAW - Pradana, Reza; Samsudin, S (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
In this research, the author aims to investigate the selection of specific materials for flooring. Flooring is typically the part that requires the longest replacement time, thus careful planning is necessary when choosing the type or material of the floor to be used. The selection of flooring should consider functional aspects, aesthetics, user comfort, safety, and health for its occupants. Therefore, in this study, the researcher will develop a recommendation system for ceramic tile selection using the fuzzy MCDM and SAW methods with multiple criteria. The criteria used include space, area, price, quality, texture, and pattern. It is expected that this recommendation system can assist customers in recommending ceramic tile types according to their preferences and within their predetermined budget. The final results of the FMADM and SAW methods are represented by the final Score (V). The final score (V) represents the best decision choice from each ranking that has been inputted into the ceramic tile selection form. From Figure 4, it can be seen that the calculations where the recommendations for selecting ceramics ara Flatinum Cream Glossy ceramics